Organizational identification and extra-role behavior: Mediating role of communal orientation and psychological well-being - Munza Latif; Muhammad Ajmal; Azmat Islam (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2023)
Organizations need competent human resources to cope with unpredictable technological and environmental changes for their survival. One of the main human resources facets is taking ownership of the organization's activities and performing extra duties for the organization's welfare. Hence, the extra role behavior of employees plays a vital role in being competitive in this complex and uncertain business environment. The study aims to find the antecedents of extra-role behavior, like organizational identification, communal orientation, psychological well-being, and perceived corporate social responsibility. This study has presented a comprehensive new behavioral mechanism model for understanding antecedents of extra-role behavior with the help of social identity theory, unlike previous studies that included a few sets of variables. For this purpose, a cross-sectional study is conducted, and a well-structured questionnaire is established to distribute to Pakistan's IT firms. The data is collected from the 383 employees working on different levels / designations in software houses / IT companies. Structural equation modeling (SEM) is used to test path analysis, and Hayes macro process is used for moderation testing. After analyzing the data, it is found that organizational identification is directly related to extra- role behavior and communal orientation; psychological well-being can also relate to their relationship by performing a role as mediators. Additionally, perceived corporate social responsibility as a moderator strengthens the relationship between organizational identification and communal orientation.
Keywords: 330; Organizational identification; extra-role behavior; communal orientation; psychological well-being; perceived corporate social responsibility; IT companies